Discovery Learning-Based Virtual Laboratory in Physics Education as an Effort to Enhance Students’ Scientific Attitudes - Liza Septia Ahmad; Zuhdan Kun Prasetyo (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to evaluate the effectiveness of using discovery-based virtual laboratories in enhancing students' scientific attitudes towards the topic of the photoelectric effect. The method employed a quasi-experimental design involving 12th-grade students at SMAN 2 Yogyakarta. The research design employed is pretest-posttest, nonequivalent multiple-group design. Subject selection was conducted through purposive sampling, resulting in experimental and control classes. The research subjects were from classes 12 MIPA 4 and 12 MIPA 5. Data were collected through questionnaires and observations of scientific attitudes. Observations during the learning process were conducted by three observers. The results of the study showed an improvement in the understanding of physics concepts and the development of scientific attitudes in the experimental group, with an average score of 89.36. The improvement in the experimental group was higher than that in the control group. These findings indicate that virtual laboratories based on discovery learning are effective in enhancing students' scientific attitudes. This finding highlights the potential of virtual laboratories in fostering scientific attitudes and assisting students in understanding modern physics, thereby stimulating their interest in the subject. The positive implications for physics education indicate that this approach can address students' challenges in learning physics conventionally